Effects of leg contrast strength training on sprint, agility and repeated change of direction performance in male soccer players - Hammami, M.; Negra, Y.; Shephard, R. J.; Chelly, M. S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Contrast training is a popular technique among individuals who are involved in dynamic sports, having as its goal an increase in dynamic muscular performance. It is characterized by the use of high and low loads in the same strength training session. The present investigation aimed to determine the effects of adding 8 weeks of contrast strength training (CSTP) to regular soccer practice in U-17 male soccer players during the competitive season. We hypothesized that CSTP would enhance their performance.